Integrating academic writing in degree programmes in higher education - Strøm, Janine Tessem; Hambro, Cathinka Dahl (Septentrio Conference Series, 2020)
Students at higher education institutions largely communicate their acquired knowledge through written assignments.The results follow the students through their career as documentation of their competence. A dimension of academic writing is to demonstrate a degree of critical thinking, as an important objective of higher education is to prepare the student for taking active part in society – a society in which the ability of critical thinking is an imperative. Despite the fact that academic writing constitutes a central part of higher education, there is little systematic follow-up on this topic in most higher education institutions in Norway. From 2018, Department of Language and Culture at UiT decided to remedy this by engaging a writing mentor who offers students support on academic writing. Additionally, the Department has chosen to emphasise the importance of writing by integrating zero-credit obligatory courses within the degree programmes in language and literature. From 2020, students will be required to follow such courses in their first, third and fifth semesters. The courses will follow the students’ progression and emphasise the demands for writing skills at the various levels of the degree. By integrating academic writing in the degree programmes, the writing mentor has a unique opportunity to develop seminars accommodated for the writing culture within the students’ own discipline in collaboration with the academic staff. The purpose is to make students better equipped to encounter the technical, formal and ethical requirements of writing in the higher education system. Another objective is to make the students aware of how academic writing and communication areconnected to critical, academic thinking. In this paper, we discuss the idea behind the integrated academic writing courses and share our experiences.